Fingerprint usage as a Text and Its Performance on Database - Yahya Ali, Nashwan (International Journal of Computer Sciences and Engineering, 2019)
Database is considered as an essential element in any organization. Many Databases contains columns, dedicated to hold information about fingerprint. Fingerprint can be stored in two ways. We can either store the path of the fingerprint image inside the database or store the fingerprint template itself as binary stream. Sometimes, database is overloaded with many requests on fingerprint column and this degrades the overall performance of the Database. To solve this problem, we take the advantage of Fingerprint conversion to text which relieves the battleneck problem and offers better performance. SQL Server is used to show the difference of Database throughput in both situation, fingerprint as image and fingerprint as text.